#### Answer

See below.

#### Work Step by Step

Using the given identities: $\cot(-\theta)=\frac{\cos(-\theta)}{\sin(-\theta)}=\frac{\cos(\theta)}{-\sin(\theta)}=-\frac{\cos(\theta)}{\sin(\theta)}=-\cot(\theta)$

Published by
McDougal Littell

ISBN 10:
0618595414

ISBN 13:
978-0-61859-541-9

See below.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.